2005
DOI: 10.1016/j.yhbeh.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in behavioural responses to stress in two strains of rainbow trout () with contrasting stress responsiveness

Abstract: The aim of this study was to establish whether two lines of rainbow trout divergent for their plasma cortisol response to a standardized stressor would show consistent differences in their behavioural response to a range of challenging situations. Our results show that the high-and low-responding (HR and LR) lines of rainbow trout did not differ in the aggression shown towards an intruder or in their response to the introduction of a novel object to their home environment. However, there was a difference in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 30 publications
6
63
2
3
Order By: Relevance
“…In addition, following transfer from group rearing to isolation in an unfamiliar tank, trout from the LR strain resumed feeding earlier than did fish from the HR strain (Øverli et al, 2002a). It was later shown that rapid resumption of feeding following transfer to a novel environment also predicts social dominance and level of aggression towards territorial intruders in non-selected aquaculture strains of rainbow trout (Øverli et al, 2004;Schjolden et al, 2005a). Most of the behavioural characteristics of the HR line are consistent with previously reported effects of the steroid hormone cortisol in non-mammalian vertebrates (Gregory and Wood, 1999;Øverli et al, 2002b;DiBattista et al, 2005).…”
Section: Walbaum 1792)supporting
confidence: 70%
“…In addition, following transfer from group rearing to isolation in an unfamiliar tank, trout from the LR strain resumed feeding earlier than did fish from the HR strain (Øverli et al, 2002a). It was later shown that rapid resumption of feeding following transfer to a novel environment also predicts social dominance and level of aggression towards territorial intruders in non-selected aquaculture strains of rainbow trout (Øverli et al, 2004;Schjolden et al, 2005a). Most of the behavioural characteristics of the HR line are consistent with previously reported effects of the steroid hormone cortisol in non-mammalian vertebrates (Gregory and Wood, 1999;Øverli et al, 2002b;DiBattista et al, 2005).…”
Section: Walbaum 1792)supporting
confidence: 70%
“…According to the aggression-boldness syndrome, animals that are more aggressive will also be bolder and more explorative in novel environments (Huntingford, 1976). Aggression-boldness has been described in many animals, including mammals (Benus et al, 1991), birds , and fish (Huntingford, 1976;Brick and Jakobsson, 2001;Schjolden et al, 2005;Moretz et al, 2007;Bourne and Sammons, 2008). However, the mechanism underlying its formation is not well understood and has been suggested to be caused by either pleiotropic genetic (Deng et al, 1994;Dingemanse et al, 2007) or hormonal (Koolhaas et al, 1999;Veenema et al, 2003) constraint or selection driven by optimal adaptation to the environment (Bell, 2005;Bell and Sih, 2007), with each behavioral component having a separate genetic basis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pottinger & Carrick (1999) selected rainbow trout (Oncorhynchus mykiss) selected for responsiveness of the HPI axis by assessing cortisol responses to repeated confinement stress, and selectively breeding animals at extremes of the endocrine response. These lines show divergent behavioural profiles, with high responding (HR) fish more frequently becoming subordinate (Øverli et al, 2005), habituating more slowly to transfer to a new tank (Øverli et al, 2005;Ruiz-Gomez et al, 2008), showing more behavioural arousal after the introduction of an intruder (Øverli et al, 2005) and more attacks to the intruder (Schjolden et al, 2005a) than low responding (LR) fish. Interestingly, differences were also observed in the intestinal mucosal barrier: Rosengren et al (2017) identified high responding trout in an ordinary hatchery population that show lower intestinal permeability during basal conditions, but this was reversed after stress.…”
Section: Coping Mechanisms and Monoamines In Fishmentioning
confidence: 99%